Anisodamine (654-1/654-2) ameliorates septic kidney injury in rats by inhibiting inflammation and apoptosis - Liu, Dong; Tang, Fei; Zhang, Li; Wan, Feng; Xu, Li-Yue; Zhang, Jing-Nan; Zhao, Xiao-Lan; Ao, Hui; Peng, Cheng (Frontiers in Pharmacology, 2024)
To investigate the protective effects of anisodamine (654-1/654-2) against acute kidney injury (AKI) in LPS-induced septic shock rats and explore its molecular mechanisms. 56 rats were randomly divided into 8 groups: control, LPS, LPS+654-1, and LPS+654-2 (1.25, 2.5 and 5 mg/kg). The model was evaluated by monitoring MAP, HR, and plasma LD levels. ELISA and biochemical assay kits were used to measure the levels of inflammatory cytokines (IL-1β, IL-6, and TNF-α) and kidney injury markers (BUN and CRE). Additionally, RNA-seq and bioinformatic analysis were performed to explore the mechanism of action of 654-1/654-2, and verification was conducted by western blotting and RT-PCR. 654-1/654-2 significantly restored the levels of MAP, HR, and plasma LD in septic shock rats. Furthermore, 654-1/654-2 (5 mg/kg) effectively ameliorated LPS-induced kidney structural damage and exhibited a dose-dependent reduction in levels of inflammatory cytokines and kidney injury markers. In addition, RNA-seq, WB, and RT-PCR analyses revealed that 654-1/654-2 exerted its effects by inhibiting the expressions of the NF-κB and MAPK pathways and activating the Pi3K/Akt/Bcl-2 signaling pathway, thereby mitigating AKI. This study suggested that 654-1/654-2 could alleviate AKI in septic shock rats by improving inflammation invasion and cell apoptosis. Notably, 654-1/654-2 collectively suppressed inflammation response through the p38/JNK/AP-1/NF-κB pathway. Additionally, 654-1 Promotes survival signaling via the Pi3K/Akt/Bcl-2 pathway, whereas 654-2 reduces apoptosis through the P53/Bax pathway.These findings provided a theoretical basis for the clinical application of 654-1/654-2 in treating organ damage caused by septic shock.